Supplemental minimal‐activity PET/CT to validate ambiguous findings with less than 1 mSv: Proof of concept. Issue 2 (19th February 2021) - Gühne, Falk; Drescher, Robert; Seifert, Philipp; Freesmeyer, Martin
Summary: Short‐term follow‐up examinations could verify ambiguous findings in PET/CT diagnostics, but are often avoided due to radiation and financial burdens. We demonstrate the feasibility of a focused, minimal‐activity PET protocol as a supplemental examination for uncertain findings after standard PET/CT. After changing conditions, e.g. patient positioning, preparation and bypassing an interval as well as a targeted tracer change, an additional examination with less than 1 mSv of additional radiation exposure was performed. Lowered administered activity of radiopharmaceuticals could be compensated by prolonged acquisition time, which was made possible by the limitation to a single body region. A sufficient visual and quantitative image quality of scans could be achieved. In all cases, the ambiguous finding could be clarified, so further diagnostic procedures or unnecessary interventions were avoided.